Real-world treatment patterns and disease control over one year in patients with inflammatory bowel disease in Brazil - Sassaki, Ligia Yukie [UNESP]; Baima, Julio Pinheiro [UNESP]; Miszputen, Sender J.; Junior, Roberto Luiz Kaiser; Faria, Mikaell Alexandre Gouvea; Catapani, Wilson R.; Bafutto, Mauro; Scotton, António S.; Zaltman, Cyrla; Gonçalves, Carolina D.; Guimaraes, Isabella Miranda; Ramos, Hagata S.; et al. (Baishideng Publishing Group, 2021)
BACKGROUND Crohn’s disease (CD) and ulcerative colitis (UC) are inflammatory bowel diseases (IBDs) with a remission-relapsing presentation and symptomatic exacerbations that have detrimental impacts on patient quality of life and are associated with a high cost burden, especially in patients with moderate-to-severe disease. The Real-world Data of Moderate-to-Severe Inflammatory Bowel Disease in Brazil (RISE BR) study was a noninterventional study designed to evaluate disease control, treatment patterns, disease burden and health-related quality of life in patients with moderate-to-severe active IBD. We report findings from the prospective follow-up phase of the RISE BR study in patients with active UC or CD. AIM To describe the 12-mo disease evolution and treatment patterns among patients with active moderate-to-severe IBD in Brazil. METHODS This was a prospective, noninterventional study of adult patients with active Crohn’s disease (CD: Harvey-Bradshaw Index ≥ 8, CD Activity Index ≥ 220), inadequate CD control (i.e., calprotectin > 200 µg/g or colonoscopy previous results), or active ulcerative colitis (UC: Partial Mayo score ≥ 5). Enrollment occurred in 14 centers from October 2016 to February 2017. The proportion of active IBD patients after 9-12 mo of follow-up, Kaplan-Meier estimates of the time to mild or no activity and a summary of treatment initiation, discontinuation and dose changes were examined. RESULTS The study included 118 CD and 36 UC patients, with mean ± SD ages of 43.3 ± 12.6 and 44.9 ± 16.5 years, respectively. The most frequent drug classes at index were biologics for CD (62.7%) and 5-aminosalicylate derivates for UC patients (91.7%). During follow-up, 65.3% of CD and 86.1% of UC patients initiated a new treatment at least once. Discontinuations/dose changes occurred in 68.1% of CD patients [median 2.0 (IQR: 2-5)] and 94.3% of UC patients [median 4.0 (IQR: 3-7)]. On average, CD and UC patients had 4.4 ± 2.6 and 5.0 ± 3.3 outpatient visits, respectively. The median time to first mild or no activity was 319 (IQR: 239-358) d for CD and 320 (IQR: 288-358) d for UC patients. At 9-12 mo, 22.0% of CD and 20.0% of UC patients had active disease. CONCLUSION Although a marked proportion of active IBD patients achieved disease control within one year, the considerable time to achieve this outcome represents an unmet medical need of the current standard of care in a Brazilian real-world setting.
Keywords: Crohn’s disease; Inflammatory bowel diseases; Prospective study; Ulcerative colitis